PEMANFAATAN GELOMBANG MIKRO PADA EKSTRAKSI BUAH - Arita Damasari (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
One of the preparations of Agrotechnology is a fruit. Fruit can be processed with non-conventional techniques by utilizing microwave technology. This study aims to analyze the use of microwaves in fruit extraction. Research methods are qualitative methods with Case Studies. Data collected by data analysis method by reducing, presenting and drawing conclusions. The results showed that the greater the temperature, power, and solvent ratio will produce fruit extraction with high levels of pectin. The solvent used is a kind of ethanol. Fruit extraction with Microwaved Assisted extraction is able to be a fast and efficient solution in producing high quality fruit extraction levels compared to processing in the traditional way.